Are people's health care needs better met when primary care is strong? A synthesis of the results of the QUALICOPC study in 34 countries. (2019) - Schäfer, Willemijn L.A.; Boerma, Wienke G.W.; van den Berg, Michael J.; De Maeseneer, Jan; De Rosis, Sabina; Detollenaere, Jens; Greß, Stefan; Heinemann, Stephanie; van Loenen, Tessa; Murante, Anna Maria; Pavlič, Danica R.; Seghieri, Chiara; et al.
Abstract: Aim: This article synthesises the results of a large international study on primary care (PC), the QUALICOPC study. Background: Since the Alma Ata Declaration, strengthening PC has been high on the policy agenda. PC is associated with positive health outcomes, but it is unclear how care processes and structures relate to patient experiences. Methods: Survey data were collected during 2011–2013 from approximately 7000 PC physicians and 70 000 patients in 34, mainly European, countries. The data on the patients are linked to data on the PC physicians within each country and analysed using multilevel modelling. Findings: Patients had more positive experiences when their PC physician provided a broader range of services. However, a broader range of services is also associated with higher rates of hospitalisations for uncontrolled diabetes, but rates of avoidable diabetes-related hospitalisations were lower in countries where patients had a continuous relationship with PC physicians. Additionally, patients with a long-term relationship with their PC physician were less likely to attend the emergency department. Capitation payment was associated with more positive patient experiences. Mono- and multidisciplinary co-location was related to improved processes in PC, but the experiences of patients visiting multidisciplinary practices were less positive. A stronger national PC structure and higher overall health care expenditures are related to more favourable patient experiences for continuity and comprehensiveness. The study also revealed inequities: patients with a migration background reported less positive experiences. People with lower incomes more often postponed PC visits for financial reasons. Comprehensive and accessible care processes are related to less postponement of care. Conclusions: The study revealed room for improvement related to patient-reported experiences and highlighted the importance of core PC characteristics including a continuous doctor–patient relationship as well as a broad range of services offered by PC physicians.